Consultation patterns and provision of contraception in general practice before teenage pregnancy: case-control study. Issue 7259 (19th August 2000) - Churchill, Dick; Allen, Jane; Pringle, Mike; Hippisley-Cox, Julia; Ebdon, Dave; Macpherson, Marion; Bradley, Sue
Abstract: Objectives: To determine patterns of consultation in general practice and provision of contraception before teenage pregnancy. Design: Case-control study, with retrospective analysis of case notes. Setting: 14 general practices in Trent region. Subjects: 240 registered patients (cases) with a recorded conception before the age of 20. Three controls per case were matched by age and practice. Main outcome measures: Consultations in general practice and provision of contraception in the 12 months before conception and recorded provision of contraception at any time before conception. Results: Overall, 223 cases (93%) had consulted a health professional at least once in the year before conception, 171 (71%) had discussed contraception in this time, and 121 (50%) had been prescribed oral contraception. Cases were more likely to have consulted in the year before conception than controls (odds ratio 2.70, 95% confidence interval 1.56 to 4.66). Most of the difference was owing to consultation for contraception. Overall, 53 cases (22%) resulted in a termination of pregnancy. Cases whose pregnancy ended in a termination were more likely to have received emergency contraception than either their controls (3.21, 1.32 to 7.79) or cases resulting in other outcomes (3.01, 1.06 to 8.51). Conclusions: Most teenagers who became pregnant attended general practice in the year before pregnancy, and many had sought contraceptive advice. The reluctance of teenagers to attend general practice for contraception may be less than previously supposed. The association between provision of emergency contraception and pregnancy ending in termination emphasises the need for continuing follow up of teenagers consulting for this form of contraception.